The Distribution of Environmental Equity: Exploring Spatial Nonstationarity in Multivariate Models of Air Toxic Releases. - Mennis, Jeremy L.; Jordan, Lisa (Annals of the Association of American Geographers, 2005)
A study was conducted to model the density of New Jersey's air toxic releases. Data were obtained from the the U.S. Environmental Protection Agency's Toxic Release Inventory (TRI). Findings revealed that the relationships among air toxic release density in New Jersey and class, employment, land use, race, and urban concentration vary considerably over space. However, findings demonstrated a positive significant relationship between air toxic releases and minorities in a large part of the state's urban and suburban areas, although this relationship is often mediated by other factors.